\(\sqrt{2}.\sqrt{x+2+3\sqrt{2x-5}}+\sqrt{2}.\sqrt{x-2-\sqrt{2x-5}=4}\)
=>\(\sqrt{2x-5+2.3\sqrt{2x-5}+9}+\sqrt{2x-5+2\sqrt{2x-5}+1}=4\)
=>\(\sqrt{\left(\sqrt{2x-5}+3\right)^2}+\sqrt{\left(\sqrt{2x-5}-1\right)^2}=4\)
=>\(|\sqrt{2x-5}+3|+|\sqrt{2x-5}-1|=4\)
roi ban xet cac truong hop cua gia tri tuyet doi de tim x
tích mình đi
ai tích mình
mình ko tích lại đâu
thanks
tích mình đi
ai tích mình
mình ko tích lại đâu
thanks
Điều kiện \(x\ge\frac{5}{2}\)
\(\sqrt{x+2+3\sqrt{2x-5}}+\sqrt{x-2-2\sqrt{2x-5}}=2\sqrt{2}\)
\(\Leftrightarrow\sqrt{2x+4+6\sqrt{2x-5}}+\sqrt{2x-4-2\sqrt{2x-5}}=4\)
\(\Leftrightarrow\sqrt{2x-5+6\sqrt{2x-5}+9}+\sqrt{2x-5-2\sqrt{2x-5}+1}=4\)
\(\Leftrightarrow\sqrt{\left(\sqrt{2x-5}+3\right)^2}+\sqrt{\left(1-\sqrt{2x-5}\right)^2}=4\)
\(\Leftrightarrow\left|\sqrt{2x-5}+3\right|+\left|1-\sqrt{2x-5}\right|=4\)
\(\Leftrightarrow\sqrt{2x-5}+3+\left|1-\sqrt{2x-5}\right|=4\)
\(\Leftrightarrow\left|1-\sqrt{2x-5}\right|=1-\sqrt{2x-5}\)
\(\Leftrightarrow1-\sqrt{2x-5}\ge0\)
\(\Leftrightarrow\sqrt{2x-5}\le1\Leftrightarrow\frac{5}{2}\le x\le3\)